METODE KALIBRASI SENSOR RATE-GYROSCOPE UNTUK IMU ROKET [CALIBRATION METHOD OF RATE-GYROSCOPE SENSOR FOR IMU ROCKET] - Wahyudi; Susanto, Adhi; Widada, Wahyu; Hadi, Sasongko Pramono (Indonesian Journal of Aerospace, 2012)
Rate-gyroscope sensor is used in the IMU to measure the rotation angle in three axes. The output of rate-gyroscope sensor is a voltage which is the angular rate, so to obtain the angle used once an integral process. The integral result of rate-gyroscope sensor depend on sampling time or the cycle time of program to get the datum, so the integral calculation depends on the processor speed of microcontroller (computer). Using of the different sampling time will affect the integral result or in other words we can say that for the same program, if we apply it to a different microcontroller, we will obtain the different calculation. This paper presents the calibration method for determining the calibration factor on the rate-gyroscope sensor, so we will get the actual angle value. The rate-gyroscope sensors on different axes have different characteristics, so each sensor needs to be calibrated. In the experiment results, the calibration factors in three axes are different in both for the clockwise rotation and counterclockwise rotation.